Fungsi Pengawasan DPRD Riau: (Dilema Kepentingan Partai Politik dan Kepentingan Publik) - Syahid, Mar (MOMENTUM : Jurnal Sosial dan Keagamaan, 2019)
The supervision function of Riau DPRD becomes stronger since otonomy has been ratified. Unhappily, the strength his of tenre directed to infiltrate the political party interest. In the after mach, the role of DPRD is n’tinan optimal fashion because it’strapped in transactiona lpolitics, which bets political party interst with public interest. Researcher, by using descriptive- analysis method, describes and analyzes the problem to look for the solution. As aresult, the supervision function of Riau DPRD on public interestis in poor support by asystem that be in dsover the legislators. Besides that, as the initiators of public policy, the legislators of tenignore the public interest, and will helda brieffor public if the rearedemons trant agitations and mass media issues tha tblow up the irwrong policies